Salix spp. Bark Hot Water Extracts Show Antiviral, Antibacterial, and Antioxidant Activities—The Bioactive Properties of 16 Clones - Tienaho, Jenni; Reshamwala, Dhanik; Sarjala, Tytti; Kilpeläinen, Petri; Liimatainen, Jaana; Dou, Jinze; Viherä-Aarnio, Anneli; Linnakoski, Riikka; Marjomäki, Varpu; Jyske, Tuula (Frontiers in Bioengineering and Biotechnology, 2021)
Earlier studies have shown that the bark of Salix species (Salicaceae family) is rich in extractives, such as diverse bioactive phenolic compounds. However, we lack knowledge on the bioactive properties of the bark of willow species and clones adapted to the harsh climate conditions of the cool temperate zone. Therefore, the present study aimed to obtain information on the functional profiles of northern willow clones for the use of value-added bioactive solutions. Of the 16 willow clones studied here, 12 were examples of widely distributed native Finnish willow species, including dark-leaved willow (S. myrsinifolia Salisb.) and tea-leaved willow (S. phylicifolia L.) and their natural and artificial hybrids. The four remaining clones were commercial willow varieties from the Swedish willow breeding program. Hot water extraction of bark under mild conditions was carried out. Bioactivity assays were used to screen antiviral, antibacterial, antifungal, yeasticidal, and antioxidant activities, as well as the total phenolic content of the extracts. Additionally, we introduce a fast and less labor-intensive steam-debarking method for Salix spp. feedstocks. Clonal variation was observed in the antioxidant properties of the bark extracts of the 16 Salix spp. clones. High antiviral activity against a non-enveloped enterovirus, coxsackievirus A9, was found, with no marked differences in efficacy between the native clones. All the clones also showed antibacterial activity against Staphylococcus aureus and Escherichia coli, whereas no antifungal (Aspergillus brasiliensis) or yeasticidal (Candida albicans) efficacy was detected. When grouping the clone extract results into Salix myrsinifolia, Salix phylicifolia, native hybrid, artificial hybrid, and commercial clones, there was a significant difference in the activities between S. phylicifolia clone extracts and commercial clone extracts in the favor of S. phylicifolia in the antibacterial and antioxidant tests. In some antioxidant tests, S. phylicifolia clone extracts were also significantly more active than artificial clone extracts. Additionally, S. myrsinifolia clone extracts showed significantly higher activities in some antioxidant tests than commercial clone extracts and artificial clone extracts. Nevertheless, the bark extracts of native Finnish willow clones showed high bioactivity. The obtained knowledge paves the way towards developing high value-added biochemicals and other functional solutions based on willow biorefinery approaches.